Sustainable agroforestry systems for the tropics; concepts and examples - Kang, B.T. (1996)
Integration of woody species with annual crops in agroforestry (AF) systems can enhance sustainability of production systems in the humid and subhumid tropics under low-input conditions. Agro-forestry has short and long-term protective and socioeconomic benefits. The various agroforestry systems can he classified based on the main component of the systems. Their structural arrangements, and based also on their functional attributes and socioeconomic scale of management and input use. Stable indigenous and prototype agroforestry systems suitable for humid and subhumid regions are available. However, they need wider testing and use.